Clinical Implementation of Automated Oxygen Titration in a Tertiary Care Hospital - Bouchard, Pierre-Alexandre; Parent-Racine, Geneviève; Paradis-Gagnon, Cassiopée; Simon, Mathieu; Lacasse, Yves; Lellouche, François; Maltais, François (Respiratory care, 2024)
When treating acute respiratory failure, both hypoxemia and hyperoxemia should be avoided. S should be monitored closely and O flows adjusted accordingly. Achieving this goal might be easier with automated O titration compared with manual titration of fixed-flow O . We evaluated the feasibility of using an automated O titration device in subjects treated for acute hypoxemic respiratory failure in a tertiary care hospital. Health-care workers received education and training about oxygen therapy, and were familiarized with an automated O titration device (FreeO ). A coordinator was available from 8:00 am to 5:00 pm during weekdays to provide technical assistance. The ability of the device to maintain S within the prescribed therapeutic window was recorded. Basic clinical information was recorded. Subjects were enrolled from November 2020 to August 2022. We trained 508 health-care workers on the use of automated O titration, which was finally used on 872 occasions in 763 subjects, distributed on the respiratory, COVID-19, and thoracic surgery wards, and in the emergency department. Clinical information could be retrieved for 609 subjects (80%) who were on the system for a median (interquartile range) of 3 (2-6) d, which represented 2,567 subject-days of clinical experience with the device. In the 82 subjects (14%) for whom this information was available, the system maintained S within the prescribed targets 89% of the time. Ninety-six subjects experienced clinical deterioration as defined by the need to be transferred to the ICU and/or requirement of high flow nasal oxygen but none of these events were judged to be related to the O device. Automated O titration could be successfully implemented in hospitalized subjects with hypoxemic respiratory failure from various causes. This experience should foster further improvement of the device and recommendations for an optimized utilization.